The kinematic study of the Bok Bak Fault Along Kedah Perak transect / Ahmad Faiz Salmanfarsi - Ahmad Faiz , Salmanfarsi (2017)
A section of Bok Bak Fault along southern Kedah and northern Perak is mapped for a detailed kinematic study of the fault. Remote sensing study shows a main NW-SE lineament crosscut by other lineament sets, and the lineament sets fit with a sinistral Riedel Shear model. The fault zone contain a main NW sinistral Bok Bak Fault set, with WNW sinistral set, NNW to NW sinistral set, NE dextral set, and E fractures. Mapping of mylonite along the fault zone reveals the presence of an early predominantly dextral strike slip movement along the shear zone. The shear zone is characterized by steep NW to W foliation with gentle to sub-horizontal NE stretching lineation deformed in the brittle-ductile domain. The shear zone is reactivated through sinistral to oblique slip movement, as shown by the overprinting of brittle faults and brittle-ductile shear zones on the mylonites. The Bok Bak Fault is reactivated as an oblique slip fault zone, resulting in crosscutting fault trend, which produce three main brittle episodes that are represented by NW and NNW faults, NE faults, and E faults. Brittle faulting is observed in both sedimentary rock unit and granite body. The faults are subsequently subjected to further reactivation, most likely during later extensional period along the fault zone, resulting in conflicting sense of movement along the fault trends. 40Ar/39Ar radiometric dating of biotite in mylonite produced a plateau age of 136.1 ± 1.4 Ma. This age is the first report of radiometric dating of the Bok Bak Fault, and here it is considered as the timing of the fault’s initiation. The Early Cretaceous age achieved is later than the timing of initiation of regional fault discussed in other studies, where the faults of was previously thought to be formed concurrently with Late Triassic Main Range granite intrusion. Based on compilation of geochronological data, the Bok Bak Fault is interpreted to be initiated in Early Cretaceous, representing a major tectonic event in Sundaland prior to the collision of India and Asia, where the continental core became cratonized and major faults were being developed. This is a long lived event that continued until Tertiary time, as evident from brittle reactivation along the fault zone. Recent reactivation of the fault is indicated by Quaternary sediment deformation and earthquake report along the fault zone.